DO PERSON-ORGANIZATIONAL FIT AND JOB CHARACTERISTICS CREATE EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT - Vidyana, Tina Ika; Darmanto, Susetyo; Hikmah, Hikmah (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to investigate the effect the person-organizational fit and job characteristics on organizational commitment, and its impact on employee performance. The sample used in the research were employees working in the Department of Cooperatives, MSME, Industry, and Trade Pemalang Regency. A total sample size of 95 respondents, was collected through proportional random sampling. The data collected was calculated using Structural Equation Modeling-Partial Least Square. The main results show organizational commitment mediates the essential factors of P-O-fit and job characteristics in influence human resource performance. The findings highlight the essential factors of P-O-fit, job characteristics, and organizational commitment in creating high employee performance. The study contributes to the Person-Environment Fit Theory witch offers theoretical implications by validating the employee performance model in the public sector.